Mapping Urban Halal Ecosystems: Developing Authentic Spatial Learning - Ahmad Athoriq; Yuswanti Ariani Wirahayu; Ravinesh Rohit Prasad (CV Bumi Spasial, 2025)
The rapid expansion of halal tourism transforms urban spaces into critical learning resources for Cultural Geography, yet empirical spatial data suitable for Contextual Teaching and Learning (CTL) remain scarce. This study evaluates the spatial potential of halal tourism in the urban core of Malang City, aiming to provide authentic didactic resources for fostering spatial literacy. Focusing on Klojen District as a